2019
DOI: 10.21203/rs.2.10199/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What do young doctors know of Palliative Care; how do they expect the concept to work?

Abstract: Objectives Discipline of palliative care is still evolving in developed parts of the world while it remains at an infantile stage in Sri Lanka which has not been formally assessed as of today. We aimed at evaluating the level of palliative care knowledge and opinions among young medical graduates. A descriptive cross-sectional study was carried out among pre-residency medical graduates of Sri Lanka through a social media based on-line survey. The pre-tested questionnaire assessed the level of knowledge on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Poor knowledge, attitudes, and practices with respect to palliative care have been reported across several other settings as well. [10][11][12][13][14][15][16][17][18][19] Providers struggled to interact with terminal patients and explain poor prognoses to patients and caregivers. Very little research has been done in this field within India, but a comprehensive study by Martis and Westhues analyzed global literature around breaking bad news and found that the level of comfort in discussing terminal disease and prognoses varied based on the cultural acceptation of death in society.…”
Section: Resultsmentioning
confidence: 99%
“…Poor knowledge, attitudes, and practices with respect to palliative care have been reported across several other settings as well. [10][11][12][13][14][15][16][17][18][19] Providers struggled to interact with terminal patients and explain poor prognoses to patients and caregivers. Very little research has been done in this field within India, but a comprehensive study by Martis and Westhues analyzed global literature around breaking bad news and found that the level of comfort in discussing terminal disease and prognoses varied based on the cultural acceptation of death in society.…”
Section: Resultsmentioning
confidence: 99%
“…Education level is the main factor affecting doctors' views on the diagnosis and management of some diseases ( 16 , 17 ). However, education level was not associated with different attitudes toward the management of MCDK among pediatric urologists and pediatric surgeons in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sri Lankan doctors are not sufficiently familiar with the unique principles of palliative care, a clinical discipline thriving in infancy in the country. [25] e sense of importance the Sri Lankan clinicians from oncology settings place on symptom alleviation as opposed to aggressive treatment of the disease is also shown to be low. [26] e palliative approach to care and the emphasis it places on ethics must form integral parts of the clinician's education and training.…”
Section: Tips From the United Kingdom (Uk)mentioning
confidence: 99%